Control System and Monitoring on Microhydro Power Plant Based on Supervisory Control and Data Acquisition - Arnita, Arnita; Hidayat, Hidayat (Southeast Asian Journal of Technology and Science, 2021)
Micro-Hydro Power Plant (MHPP), is a micro power plant operate by water flow to rotate the turbine  generate the desired power. The amount of electricity generated by the MHPP needs to be maintained to continuous for customer convenience.  The water debit will have the effect to the amount of electricity generated by the MHPP. Therefore, monitoring and supervision is required for MHPP system operation. In general monitoring and supervision of the MHPP system by checking the amount of electricity generated. Currently, to control of turbine blades still done by manually. To do that it is requires a personnel and fixed time even though the area is far from human. In order to facilitate monitoring and supervision, it is necessary to have a control and monitoring system. Which is control and monitoring will be done remotely using supervisory control and data acquisition (SCADA) system. The main parts of SCADA are Master Station (MS), Remote Terminal Unit (RTU) & Communication System. Communication System in SCADA can be built in several options both wired and wireless. From that, the authors make a tool used to monitor the amount of electricity and control of the turbine blades MHPP that can be done through internet service. As data processing, Arduino is used for monitoring and controlling system. For data communication used Arduino Ethernet Shield in the form of internet communication. The use of this control system makes it easy for users when it comes to monitoring and control.